Restenosis after stenting in symptomatic vertebral arterial orifice disease and considerations for better outcome. Issue 2 (April 2017) - Chang, Jun Young; Park, Hyun; Kwon, Oki; Han, Moon-Ku
We have performed stenting in 11 patients with symptomatic vertebral arterial orifice stenosis refractory to medical treatment or impairment in anterior circulation. Three of the 11 patients experienced asymptomatic severe in-stent restenosis or occlusion. Bare metal stents were used in those three patients, two of whom received revascularization therapy. Development of sufficient cervical collateral channels reconstituting the distal vertebral artery was the common feature in patients with asymptomatic in-stent restenosis. In selecting appropriate stents, consideration of mechanical strength and drug-eluting properties of a stent according to characteristics of the target vessel is important to reduce the risk of in-stent restenosis. Any decision to perform revascularization should be based on the presence of abundant cervical collaterals as well as clinical symptoms of vertebrobasilar ischemia.